DEVELOPMENT OF BUILDING INFORMATION MODELING TECHNOLOGIES AND THEIR IMPLEMENTATION IN THE FIELD OF MODERN RUSSIAN DESIGN - Skripkina, Julia; Mishchenko, Olga; Velikanov, Alexander (Journal of Applied Engineering Science, 2019)
This article discusses a brief history of computer design in general and BIM (Building Information Modeling) in particular. The main benefits of BIM are shown. The benefits of their implementation in Russian architectural and design organizations are justified
Keywords: architecture; modeling; structures; buildings; design; computer program